Three-dimensional Discrete Element Simulation of Interaction between Aqueduct and Tunnel - Sarfarazi, Vahab; Haeri, Hadi; Asgari, Kaveh (Periodica Polytechnica Civil Engineering, 2022)
In this investigation the effect of interaction between aqueduct and tunnel on the ground settlement has been examined using PFC3D. At first, the calibration of PFC3D was conducted based on UCS test results rendered from three different ground layer. Then intact model with dimension of 70 m × 20 m × 34.5 m (x × y × z) was built. These models are consisted of 8 layers with different mechanical and geometrical properties. Four different configurations for aqueduct were created in four models. Diameter of aqueduct was 2 m and its depth was different in four models. After aqueduct generation, tunnel with diameter of 9 m and length of 20 m was drilled in depth of 22 m. After tunnel drilling, the settlement data of ground surface were picked up. After tunnel simulation, the effect of support lining was investigated on the ground settlement. For this purpose, after each step of tunnel drilling, lining support with diameter of 35 cm was performed. The results show that the maximum value of settlement occurred when aqueduct reach to head of tunnel. Also the safety has maximum value when the distance between aqueduct and tunnel wall was 4.5 m. the ground settlement before and after support lining shows that ground settlement reach to zero by support application.